High-transparency rare earth ultraviolet shielding material as well as preparation method and application thereof

By applying porous polyetherimide to coat rare earth silicate materials and highly transparent rare earth shielding materials on textiles, the existing UV-resistant textile materials have solved the problems of strong hiding power, high transmittance and unstable physical and chemical properties, and textile materials with high transparency, good heat insulation and anti-aging properties have been achieved.

CN119708938APending Publication Date: 2025-03-28TIANJIN BAOGANG RES INST OF RARE EARTHS CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510026044.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Existing UV-resistant textile materials have problems such as strong hiding power, high transmittance and unstable physical and chemical properties, making it difficult to maintain high transparency and high temperature stability.

Method used

A high-transparent rare earth silicate material is coated with porous polyetherimide and a high-transparent rare earth shielding material. A high-transparent rare earth ultraviolet shielding material is prepared by a combination of primer and topcoat, and nano-scale powder is prepared by spray drying.

Benefits of technology

It achieves high absorption capacity in the 280-400nm band, with a transmittance of ≤1%, and the transmittance of visible light and near-infrared light is basically unchanged, ensuring that the original color of the fabric is not affected, and at the same time it has good heat insulation and anti-aging properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708938A_ABST
    Figure CN119708938A_ABST
Patent Text Reader

Abstract

The invention provides a high-transparency rare earth ultraviolet shielding material as well as a preparation method and application thereof. The high-transparency rare earth ultraviolet shielding material comprises a base coating and a surface coating, the primer comprises a porous polyetherimide coated rare earth silicate material, first water-based resin, a first pre-dispersing agent, a first auxiliary agent and deionized water; the surface coating comprises a high-transparency rare earth shielding material, 10-50 parts of second water-based resin, a second pre-dispersing agent, a second auxiliary agent and deionized water; wherein the rare earth silicate is (LaaYbSmcDyd) 2Si2O7, a, b, c and d are more than 0 and less than 1, and a + b + c + d = 1; the high-transparency rare earth shielding material is LamCenYxAl2B2SiO8 (OH) 2, 0 lt, and the total amount of the rare earth shielding material is 100%. M, n, xlt; and m + n + x is equal to 0.67. The material can effectively block and radiate sunlight radiation heat, reduces the temperature of the surface of the fabric and the interior of the fabric, and is a preferable material for summer sunscreen clothes, outdoor mountaineering jackets and swimsuits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of functional materials, and in particular relates to a highly transparent rare earth ultraviolet shielding material and a preparation method and application thereof. Background Art

[0002] The earth is always exposed to sunlight, which includes infrared light, visible light and ultraviolet light. Ultraviolet light is emitted from the sun through the atmosphere to the earth's surface. The intensity of ultraviolet light in different regions varies due to the altitude, the concentration of the ozone layer and the weather. In summer and plateau areas, the intensity of ultraviolet light is higher than in other cases. Appropriate ultraviolet light can promote metabolism in the body, enhance the body's absorption of calcium, and also has the effect of sterilization and removal of mites. However, with the rapid development of industrialization and frequent human activities in recent years, the environment has been severely affected. Nitrogen oxides produced by industrial waste gas and automobile exhaust, as well as gases such as Freon used in people's lives, have caused the loss of the ozone layer (ultraviolet absorption protection layer), weakened the protection of the ozone layer, and made the ultraviolet radiation from the sun to the surface stronger. Long-term exposure to ultraviolet light will cause irreversible damage to the human body and objects. Therefore, it is extremely important to strengthen the protection against ultraviolet light in life for our health and safety. Clothing products with anti-ultraviolet light can effectively reduce the damage of outdoor personnel under ultraviolet light, especially in summer, at the seaside and in some special working environments with strong ultraviolet light. Research on giving textiles excellent anti-ultraviolet properties is imminent.

[0003] Currently, UV-resistant textiles are mainly given UV protection through finishing technology, a process that involves applying functional additives to the fabric. These additives are generally divided into two categories: organic UV screeners and inorganic UV screeners. Compared with organic types, inorganic UV screeners are preferred due to their higher safety, stability and wider UV absorption range.

[0004] Common inorganic UV shielding agents include titanium dioxide (TiO2), cerium dioxide (CeO2) and zinc oxide (ZnO). However, one disadvantage of these materials is that their strong hiding ability may change the original color of the fabric. Therefore, it becomes crucial to develop a new inorganic UV shielding material that can maintain high transparency while withstanding high temperatures, strong stability and a wide UV absorption range. Summary of the invention

[0005] In view of this, the present invention aims to propose a highly transparent rare earth UV shielding material and a preparation method and application thereof, so as to solve the problems in the prior art such as strong covering power, high UV transmittance, and unstable physical and chemical properties of anti-UV components.

[0006] To achieve the above object, the technical solution of the present invention is achieved as follows:

[0007] A highly transparent rare earth ultraviolet shielding material, comprising a primer and a topcoat;

[0008] The primer comprises the following components in parts by weight: 20-50 parts of porous polyetherimide coated rare earth silicate material, 10-50 parts of a first aqueous resin, 0.1-5 parts of a first pre-dispersant, 1-10 parts of a first auxiliary agent, and 10-30 parts of deionized water;

[0009] The top coating comprises the following components in parts by weight: 20-50 parts of a highly transparent rare earth shielding material, 10-50 parts of a second aqueous resin, 0.1-5 parts of a second pre-dispersant, 1-10 parts of a second auxiliary agent, and 10-30 parts of deionized water;

[0010] Among them, rare earth silicates are (La a Y b Sm c Dy d )2Si2O7, 0<a,b,c,d<1, a+b+c+d=1; high transparent rare earth shielding material is La m Ce n Y x Al2B2SiO8(OH)2,0 <m,n,x<0.67,m+n+x=0.67。

[0011] Furthermore, the porous polyetherimide-coated rare earth silicate material is prepared by the following method:

[0012] 1) Weigh rare earth oxide and silicon oxide, mix them evenly according to a certain proportion, and then add deionized water to mix;

[0013] 2) putting the prepared material in step 1) into a ball mill for ball milling, taking out the material after the milling, and drying it to obtain a rare earth silicate precursor;

[0014] 3) The rare earth silicate precursor obtained in step 2) is placed in a tube furnace and calcined to obtain rare earth silicate (La a Y b Sm c Dy d )2Si2O7;

[0015] 4) grinding the rare earth silicate obtained in step 3);

[0016] 5) dissolving the polyetherimide particles in N-methylpyrrolidone to obtain a transparent dark yellow polyetherimide solution;

[0017] 6) Weigh rare earth silicate and polyetherimide solution, mix them evenly and stir them ultrasonically, centrifuge and dry after the reaction to obtain a porous polyetherimide-coated rare earth silicate material.

[0018] Further, in step 2), the ball milling speed is 300-600 r / min, the ball milling reaction is 12-18 hours, and the mixture is dried at 60-80° C. for 8-12 hours;

[0019] In step 3), the calcination temperature is 1200-1500° C. and the calcination time is 3-6 hours;

[0020] In step 4), the particle size after grinding is 500-800 nm;

[0021] In step 5), the dissolution temperature of the polyetherimide particles is 50-70°C;

[0022] In step 6), ultrasonic stirring is performed for 20-60 minutes, and the drying temperature is 60-80°C.

[0023] Further, in step 1), the molar ratio of rare earth oxide to silicon oxide is 1:2;

[0024] The rare earth oxide is a mixture of lanthanum oxide, yttrium oxide, dysprosium oxide and samarium oxide;

[0025] In step 6), 50-70 parts of rare earth silicate and 30-50 parts of polyether imide solution are included by weight.

[0026] Furthermore, the highly transparent rare earth shielding material is prepared by the following method:

[0027] 1) Weigh boric acid, silicon oxide, rare earth oxide and aluminum oxide into a ball mill, and add deionized water to mix;

[0028] 2) putting the prepared materials in step 1) into a ball mill for ball milling;

[0029] 3) The ball-milled material in step 2) is filtered, washed and dried to obtain La m Ce n Y x Al2B2SiO8(OH)2 powder is then placed in a tube furnace and calcined to obtain a block of La m Ce n Y x Al2B2SiO8(OH)2;

[0030] 4) Add deionized water to the material obtained in step 3), and then add block La m Ce n Y x A grinding dispersant with a mass percentage of 1-8% of Al2B2SiO8(OH)2 is ground to a particle size of ≤100nm to obtain a highly transparent rare earth shielding material slurry;

[0031] 5) The highly transparent rare earth shielding material slurry obtained in step 4) is formed into nano-scale powder by a spray dryer.

[0032] Further, in step 1), the molar ratio of boric acid: silicon oxide: aluminum oxide: rare earth oxide is 1:1:1:0.67; the rare earth oxide is a mixture of lanthanum oxide, cerium oxide and yttrium oxide;

[0033] In step 2), the ball milling speed is 300-800 r / min, and the ball milling is 8-16 hours;

[0034] In step 3), the drying temperature is 60-80°C, the calcination temperature is 400-600°C, and the calcination time is 3-6;

[0035] In step 4), the grinding dispersant is fatty acid polyethylene glycol ester;

[0036] Step 5) The powder particle size obtained after spray drying is 400-600nm.

[0037] Furthermore, the first water-based resin and the second water-based resin are both selected from one or more of acrylic resin, polyurethane resin, pure acrylic emulsion, and silicon-modified acrylic emulsion;

[0038] The first pre-dispersant and the second pre-dispersant are both selected from one or more of BYK-2013, BYK-190, sodium hexametaphosphate, sodium pyrophosphate, and polyvinyl alcohol;

[0039] The first auxiliary agent and the second auxiliary agent are both selected from one or more of a wetting agent, a thickener, a leveling agent, a defoaming agent, an anti-settling agent, and a film-forming auxiliary agent.

[0040] The present invention also provides a method for preparing the highly transparent rare earth ultraviolet shielding material as described above, the method comprising the following steps:

[0041] 1) Preparation of primer

[0042] 1.1) Weigh the first aqueous resin, the first pre-dispersant and deionized water and stir and disperse them for 60-90 minutes;

[0043] 1.2) adding the porous polyetherimide-coated rare earth silicate material to step 1.1) and stirring and dispersing for 60-90 minutes, then adding the first auxiliary agent and continuing stirring for 10-30 minutes to prepare a primer;

[0044] 2) Preparation of topcoat

[0045] 2.1) Weigh the second aqueous resin, the second pre-dispersant and deionized water and stir and disperse for 60-90 minutes;

[0046] 2.2) Add the highly transparent rare earth shielding material to step 2.1) and stir and disperse for 60-90 minutes, then add the second auxiliary agent and continue stirring for 10-30 minutes to obtain the top coating.

[0047] The present invention also provides an application of the highly transparent rare earth ultraviolet shielding material as described above in the fields of home textiles, outdoor products, clothing fabrics and industrial textiles. When applied, the primer is scraped on the surface of the fabric and cured at 130-150°C for 3-5 minutes to complete the coating of the primer; the topcoat is scraped on the surface of the primer and cured at 130-150°C for 3-5 minutes to complete the coating of the topcoat.

[0048] Furthermore, the weight of the primer coating is 40-55 g / m 2 The weight of the intermediate and top coatings should be kept at 15-25g / m 2 between.

[0049] Compared with the prior art, the highly transparent rare earth ultraviolet shielding material and the preparation method thereof described in the present invention have the following advantages:

[0050] (1) The highly transparent rare earth ultraviolet shielding material of the present invention has excellent selective shielding properties for light. The material has strong absorption capacity in the 280-400nm band, with a transmittance of ≤1%, while the transmittance for visible light and near-infrared light remains basically unchanged. Applying it on the surface of fabric can not only protect against ultraviolet rays and anti-aging, but also ensure that the original color of the fabric is not affected.

[0051] (2) The present invention prepares a porous polyetherimide-coated rare earth silicate material by surface modification. As a thermal insulation material, the porous polyetherimide-coated rare earth silicate material has a unique microporous particle structure, coupled with multiple scattering and surface phonon polaritons. When the porous polyetherimide-coated rare earth silicate material is coated on the surface of a fabric, the coating has a solar reflectivity of 91% and an emissivity of 96% in the 8-14 μm band. The coating can effectively block and radiate solar radiation heat, thereby reducing the temperature of the fabric surface and the bottom of the fabric.

[0052] (3) The present invention prepares a highly transparent rare earth shielding material with a hollow structure of nano-scale powder by adopting a spray drying process. When the material is formulated into a coating and applied to the surface of a fabric, a static air layer is formed between the nano-powders, which greatly reduces the thermal conductivity of the coating, thereby effectively preventing the conduction of heat.

[0053] (4) The highly transparent rare earth shielding material and porous polyetherimide-coated rare earth silicate material prepared by the present invention are both obtained after high-temperature calcination, and have stable physical and chemical properties. The coated fabric prepared thereby has strong weather resistance and is not easy to decompose. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:

[0055] Figure 1 This is a SEM image of the UV-proof heat-insulating coating fabric prepared in Example 1;

[0056] Figure 2 The highly transparent rare earth shielding material La prepared in Example 1 0.67 / 3 Ce 0.67 / 3 Y 0.67 / 3 SEM image of Al2B2SiO8(OH)2. DETAILED DESCRIPTION

[0057] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.

[0058] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0059] Example 1 Highly transparent rare earth ultraviolet shielding material and its preparation

[0060] A highly transparent rare earth ultraviolet shielding material, comprising a primer and a topcoat;

[0061] The primer comprises the following components in parts by weight: 30 parts of porous polyetherimide-coated rare earth silicate material, 15 parts of acrylic resin, 15 parts of waterborne polyurethane resin, 2 parts of BYK-2013, 2 parts of thickener, 2 parts of film-forming aid, 2 parts of wetting agent, 2 parts of defoamer, and 30 parts of deionized water;

[0062] The topcoat includes the following components in parts by mass: 20 parts of highly transparent rare earth shielding material, 40 parts of water-based acrylic resin, 3 parts of sodium hexametaphosphate, 2 parts of anti-settling agent, 2 parts of film-forming aid, 1 part of wetting agent, 1 part of defoaming agent, 1 part of leveling agent, and 30 parts of deionized water.

[0063] Wherein, the porous polyetherimide coated rare earth silicate material is prepared by the following method:

[0064] 1) Weigh lanthanum oxide, yttrium oxide, samarium oxide, dysprosium oxide and silicon oxide in a molar ratio of 0.25:0.25:0.25:0.25:2, mix well, and add deionized water to make the solid content 50%;

[0065] 2) The prepared material in step 1) was put into a ball mill and milled at a speed of 500 r / min for 15 hours. After the milling reaction was completed, the material was taken out and dried at 70° C. for 12 hours to obtain a rare earth silicate precursor;

[0066] 3) The rare earth silicate precursor obtained in step 2) is placed in a tube furnace and calcined at 1450°C for 5 hours to obtain rare earth silicate (La 0.25 Y 0.25 Sm 0.25 Dy 0.25 )2Si2O7;

[0067] 4) grinding the rare earth silicate obtained in step 3) to a particle size of 500-800 nm;

[0068] 5) dissolving the polyetherimide particles in N-methylpyrrolidone at 60° C. to obtain a transparent dark yellow polyetherimide solution;

[0069] 6) Weigh 60 parts of rare earth silicate (La 0.25 Y 0.25 Sm 0.25 Dy 0.25 )2Si2O7 and 40 parts of polyetherimide solution, mix the two evenly and stir ultrasonically for 40 minutes. After the reaction is completed, centrifuge and then dry at 70°C and 60% relative humidity for 12 hours to obtain a porous polyetherimide-coated rare earth silicate material.

[0070] The highly transparent rare earth shielding material is prepared by the following method:

[0071] 1) weighing lanthanum oxide, cerium oxide, yttrium oxide, boric acid, silicon oxide and aluminum oxide in a molar ratio of 0.67 / 3:0.67 / 3:0.67 / 3:1:1:1 and putting them into a ball mill, and adding an appropriate amount of deionized water; 2) putting the materials prepared in step 1) into a ball mill and milling them at a speed of 700 r / min for 15 hours;

[0072] 3) The ball-milled material in step 2) is filtered, washed, and dried at 60°C to obtain La 0.67 / 3 Ce 0.67 / 3 Y 0.67 / 3Al2B2SiO8(OH)2 powder, which was then placed in a tube furnace and calcined at 600℃ for 5 hours to obtain bulk La 0.67 / 3 Ce 0.67 / 3Y 0.67 / 3 Al2B2SiO8(OH)2;

[0073] 4) Deionized water was added to the material obtained in step 3) to make the solid content reach 50%, and then block La was added thereto. 0.67 / 3 Ce0.67 / 3 Y 0.67 / 3 Al2B2SiO8(OH)2 is ground with a grinding dispersant of 5% by mass of fatty acid polyethylene glycol ester to a particle size of ≤100nm to obtain a highly transparent rare earth shielding material slurry;

[0074] 5) The highly transparent rare earth shielding material slurry obtained in step 4) is formed into nano-scale powder with a particle size of ≤500nm by a spray dryer.

[0075] like Figure 2 Highly transparent rare earth shielding material La 0.67 / 3 Ce 0.67 / 3 Y 0.67 / 3 SEM image of Al2B2SiO8(OH)2 shows La 0.67 / 3 Ce 0.67 / 3 Y 0.67 / 3 Al2B2SiO8(OH)2 is a nanoparticle with a hollow structure.

[0076] The preparation method of the above-mentioned highly transparent rare earth ultraviolet shielding material comprises the following steps:

[0077] 1) Preparation of primer

[0078] 1.1) Weigh 15 parts of acrylic resin, 15 parts of waterborne polyurethane resin, 2 parts of BYK-2013 and 30 parts of deionized water and stir and disperse for 80 minutes;

[0079] 1.2) adding 30 parts of porous polyetherimide coated rare earth silicate material to step 1.1) and stirring and dispersing for 80 minutes, then adding the first auxiliary agent 2 parts of thickener, 2 parts of film-forming auxiliary, 2 parts of wetting agent, 2 parts of defoamer and continuing stirring for 30 minutes to prepare a primer;

[0080] 2) Preparation of topcoat

[0081] 2.1) Weigh 40 parts of water-based acrylic resin, 3 parts of sodium hexametaphosphate and 30 parts of deionized water and stir and disperse for 80 minutes;

[0082] 2.2) Add 20 parts of highly transparent rare earth shielding material to step 2.1) and stir and disperse for 80 minutes, then add the second additive, 2 parts of anti-settling agent, 2 parts of film-forming aid, 1 part of wetting agent, 1 part of defoaming agent and 1 part of leveling agent, and continue stirring for 30 minutes to obtain a topcoat.

[0083] When in use, the primer is scraped on the fabric surface and cured at 140°C for 5 minutes to complete the coating of the primer; the topcoat is scraped on the surface of the primer and cured at 140°C for 5 minutes to complete the coating of the topcoat, thus completing the preparation of the anti-ultraviolet heat insulation coating fabric. The weight gain of the primer coating is 50g / m 2The additional weight of the top coating is 20g / m 2 .

[0084] like Figure 1 This is the SEM image of the prepared UV-proof and heat-insulating coating fabric.

[0085] Example 2

[0086] Based on the above Example 1, the molar ratio of lanthanum oxide, yttrium oxide, samarium oxide, dysprosium oxide and silicon oxide in preparing the porous polyetherimide coated rare earth silicate material is 0.20:0.30:0.28:0.22:2, and the obtained rare earth silicate is (La 0.20 Y 0.30 Sm 0.28 Dy 0.22 )2Si2O7;

[0087] The molar ratio of lanthanum oxide, cerium oxide, yttrium oxide, boric acid, silicon oxide and aluminum oxide for preparing highly transparent rare earth shielding material is 0.15:0.35:0.17:2:1:2. The highly transparent rare earth shielding material obtained is La 0.15 Ce 0.35 Y 0.17 Al2B2SiO8(OH)2.

[0088] Example 3

[0089] Based on the above Example 1, the molar ratio of lanthanum oxide, yttrium oxide, samarium oxide, dysprosium oxide and silicon oxide in preparing the porous polyetherimide coated rare earth silicate material is 0.10:0.40:0.15:0.35:2, and the obtained rare earth silicate is (La 0.10 Y 0.40 Sm 0.15 Dy 0.35 )2Si2O7;

[0090] The molar ratio of lanthanum oxide, cerium oxide, yttrium oxide, boric acid, silicon oxide and aluminum oxide for preparing highly transparent rare earth shielding material is 0.25:0.15:0.27:2:1:2. The highly transparent rare earth shielding material obtained is La 0.25 Ce 0.15 Y 0.27 Al2B2SiO8(OH)2.

[0091] Example 4

[0092] On the basis of the above-mentioned embodiment 1, the primer comprises the following components in parts by weight: 40 parts of porous polyetherimide-coated rare earth silicate material, 15 parts of acrylic resin, 15 parts of waterborne polyurethane resin, 3 parts of BYK-2013, 4 parts of thickener, 2 parts of film-forming aid, 1 part of wetting agent, 1 part of defoamer, and 19 parts of deionized water;

[0093] The topcoat includes the following components in parts by mass: 21 parts of highly transparent rare earth shielding material, 45 parts of water-based acrylic resin, 3 parts of sodium hexametaphosphate, 1 part of anti-settling agent, 3 parts of thickener, 2 parts of film-forming aid, 1 part of wetting agent, 1 part of defoamer, 1 part of leveling agent, and 25 parts of deionized water.

[0094] Example 5

[0095] On the basis of the above-mentioned Example 1, the first aqueous resin and the second aqueous resin are both silicon-modified acrylic emulsions.

[0096] Comparative Example 1

[0097] The difference from Example 1 is that the thermal insulation component porous polyetherimide coated rare earth silicate material and the UV protection component highly transparent rare earth shielding material are not added. The specific preparation steps are as follows:

[0098] 1) Preparation of primer

[0099] 1.1) Weigh 22.5 parts of acrylic resin, 22.5 parts of waterborne polyurethane resin, 2 parts of BYK-2013 and 45 parts of deionized water and stir and disperse for 80 minutes;

[0100] 1.2) adding 2 parts of thickener, 2 parts of film-forming aid, 2 parts of wetting agent and 2 parts of defoamer to step 1.1) and continuing stirring for 30 minutes to prepare a primer;

[0101] 2) Preparation of topcoat

[0102] 2.1) Weigh 50 parts of water-based acrylic resin, 3 parts of sodium hexametaphosphate and 40 parts of deionized water and stir and disperse for 80 minutes;

[0103] 2.2) Add 2 parts of anti-settling agent, 2 parts of film-forming aid, 1 part of wetting agent, 1 part of defoaming agent and 1 part of leveling agent to step 2.1) and continue stirring for 30 minutes to obtain a topcoat.

[0104] Comparative Example 2

[0105] The difference from Example 1 is that the thermal insulation component porous polyetherimide coated rare earth silicate material is not added to the primer, and the topcoat formula remains unchanged.

[0106] Preparation of base coating:

[0107] 1) Weigh 22.5 parts of acrylic resin, 22.5 parts of waterborne polyurethane resin, 2 parts of BYK-2013 and 45 parts of deionized water and stir and disperse for 80 minutes;

[0108] 2) Add 2 parts of thickener, 2 parts of film-forming aid, 2 parts of wetting agent and 2 parts of defoamer into step 1) and continue stirring for 30 minutes to prepare a primer.

[0109] Comparative Example 3

[0110] The difference from Example 1 is that the formula of the primer remains unchanged, and the UV protection component highly transparent rare earth shielding material is not added to the topcoat.

[0111] Preparation of topcoat:

[0112] 1) Weigh 50 parts of water-based acrylic resin, 3 parts of sodium hexametaphosphate and 40 parts of deionized water and stir and disperse for 80 minutes;

[0113] 2) Add 2 parts of anti-settling agent, 2 parts of film-forming aid, 1 part of wetting agent, 1 part of defoaming agent and 1 part of leveling agent to step 1) and continue stirring for 30 minutes to obtain a topcoat.

[0114] Comparative Example 4

[0115] The difference from Example 1 is that the rare earth silicate prepared in the primer is not coated with porous polyetherimide, and the rare earth silicate material is obtained after calcination and grinding, and the formula of the topcoat remains unchanged.

[0116] Comparative Example 5

[0117] The difference from Example 1 is that the ultraviolet protection component highly transparent rare earth shielding material in the top coating is La obtained by directly drying in an oven in step 3). 0.67 / 3 Ce 0.67 / 3 Y 0.67 / 3 Al2B2SiO8(OH)2, no more calcination and spray drying, the primer remains unchanged.

[0118] Comparative Example 6

[0119] The difference from Example 1 is that the rare earth oxides in the porous polyetherimide-coated rare earth silicate material are lanthanum oxide, yttrium oxide, and samarium oxide, and the molar ratio of lanthanum oxide, yttrium oxide, samarium oxide, and silicon oxide is 1 / 3:1 / 3:1 / 3:2, and the top coating remains unchanged.

[0120] Comparative Example 7

[0121] The difference from Example 1 is that the rare earth oxides in the porous polyetherimide-coated rare earth silicate material are lanthanum oxide, yttrium oxide, and dysprosium oxide, and the molar ratio of lanthanum oxide, yttrium oxide, dysprosium oxide, and silicon oxide is 1 / 3:1 / 3:1 / 3:2, and the top coating remains unchanged.

[0122] Comparative Example 8

[0123] The difference from Example 1 is that the rare earth oxides in the porous polyetherimide-coated rare earth silicate material are lanthanum oxide, samarium oxide, and dysprosium oxide, the molar ratio of lanthanum oxide, samarium oxide, dysprosium oxide, and silicon oxide is 1 / 3:1 / 3:1 / 3:2, and the top coating remains unchanged.

[0124] Comparative Example 9

[0125] The difference from Example 1 is that the molar ratio of lanthanum oxide, yttrium oxide, samarium oxide, dysprosium oxide and silicon oxide in the porous polyetherimide-coated rare earth silicate material is 1:1:1:1:1.

[0126] Comparative Example 10

[0127] The difference from Example 1 is that the rare earth oxides in the high-transparency rare earth shielding material are lanthanum oxide and cerium oxide, the molar ratio of lanthanum oxide, cerium oxide, boric acid, silicon oxide and aluminum oxide is 0.67 / 2:0.67 / 2:1:1:1, and the primer remains unchanged.

[0128] Comparative Example 11

[0129] The difference from Example 1 is that the rare earth oxides in the high-transparency rare earth shielding material are lanthanum oxide and yttrium oxide, the molar ratio of lanthanum oxide, yttrium oxide, boric acid, silicon oxide and aluminum oxide is 0.67 / 2:0.67 / 2:1:1:1, and the primer remains unchanged.

[0130] Comparative Example 12

[0131] The difference from Example 1 is that the rare earth oxides in the high-transparency rare earth shielding material are cerium oxide and yttrium oxide, the molar ratio of cerium oxide, yttrium oxide, boric acid, silicon oxide and aluminum oxide is 0.67 / 2:0.67 / 2:1:1:1, and the primer remains unchanged.

[0132] Comparative Example 13

[0133] The difference from Example 1 is that the molar ratio of lanthanum oxide, cerium oxide, yttrium oxide, boric acid, silicon oxide and aluminum oxide in the high-transparency rare earth shielding material is 1:1:1:1:1:1, and the primer remains unchanged.

[0134] The reflectivity, emissivity, heat shielding rate, UV transmittance and UPF value of the anti-ultraviolet heat-insulating coating fabrics prepared in Examples 1-5 and Comparative Examples 1-13 were tested, and the results are shown in Table 1.

[0135] Table 1 Comparison of performance indicators of Examples 1-5 and Comparative Examples 1-12

[0136]

[0137]

[0138] It can be seen from the data in Table 1 that the anti-ultraviolet and heat-insulating coated fabrics prepared by Examples 1-5 have a UPF value greater than 400, a UV transmittance less than 1%, and a heat-shielding rate greater than 45%, and have excellent anti-ultraviolet and heat-shielding functions.

[0139] By comparing Example 1 with Comparative Examples 1-3, it can be seen that adding porous polyetherimide-coated rare earth silicate material and highly transparent rare earth shielding material to the primer and topcoat respectively can effectively improve the UV protection and heat shielding effects of the fabric.

[0140] As shown in Comparative Example 4, if the heat-insulating component in the primer is only rare earth silicate (La 0.25 Y 0.25 Sm 0.25 Dy 0.25 )2Si2O7, the surface is not coated with porous polyetherimide, although it also has a certain heat-shielding effect, but the heat-shielding property is reduced. This shows that the microporous structure on the surface of the material can couple multiple scattering and surface phonon polaritons, improve the solar reflectance of the fabric and the emissivity in the 8-14μm band, effectively block the solar radiation heat, and thus reduce the temperature on the surface and inside the fabric.

[0141] It can be seen from Comparative Example 5 that the highly transparent rare earth shielding material prepared by simple drying and crushing is larger in size. Under the condition of the same addition amount, the coverage rate of the ultraviolet shielding material on the fabric surface is low, which makes the ultraviolet transmittance high and the UPF value will be reduced accordingly.

[0142] By comparing Example 1 with Comparative Examples 6-8, it can be seen that only by adding rare earth elements to the porous polyetherimide-coated rare earth silicate material according to the scheme of the present application can the reflectivity, emissivity and heat-shielding effect of the coated fabric be improved. This is because different rare earth ions have different responses to light of specific wavelengths. Therefore, by reasonably matching a variety of rare earth elements, the material can have a reflective effect on a wider range of spectra, thereby improving the overall reflectivity; second, because each rare earth element usually has its characteristic emission wavelength, by combining different rare earth elements, emission light covering a wider spectral range can be obtained; third, the presence of a variety of rare earth elements in rare earth silicates will form a more complex crystal structure and grain boundaries, which helps to increase phonon scattering, thereby reducing the thermal conductivity of the material, and thus showing better thermal insulation performance. In addition, different rare earth elements in multi-component rare earth silicates may introduce more types of defects or impurities, which can hinder the propagation of heat flow, increase the thermal resistance of the material, and thus improve the thermal insulation effect.

[0143] By comparing Example 1 with Comparative Examples 10-12, it can be seen that only by adding rare earth elements to the high-transparency rare earth shielding material according to the scheme of the present application can the UV protection effect of the fabric be improved. This is because different rare earth elements have different absorption bands of ultraviolet rays. By mixing multiple rare earth elements, absorption of a wider range of ultraviolet rays can be achieved, including UVA (long-wave ultraviolet rays), UVB (medium-wave ultraviolet rays) and even part of UVC (short-wave ultraviolet rays), which can provide more comprehensive UV protection. In addition, different rare earth elements in multi-component rare earth silicates may produce synergistic effects. In addition to improving UV absorption, other properties may also be improved, such as increasing the material's anti-aging properties, improving wear resistance or enhancing color stability.

[0144] By comparing Example 1 with Comparative Example 9, it can be seen that too high a rare earth element ratio will also reduce the reflectivity, emissivity, and heat shielding properties of the fabric, mainly because excessive rare earth elements may increase the chemical reactivity of the material, especially in a high temperature or humid environment. This may cause the material to react with other substances (such as moisture or oxygen in the air), thereby affecting its thermal insulation performance.

[0145] By comparing Example 1 with Comparative Example 13, it can be seen that changing the rare earth element content will also reduce the UV resistance of the fabric. This is mainly because if the proportion of rare earth elements is too high or too low, the absorption band of the material may be changed, thereby affecting its absorption efficiency of ultraviolet rays of a specific wavelength, resulting in uneven UV protection performance and poor UV protection effect. In addition, if the element ratio is unbalanced, the photostability of the raw materials may be reduced, making the material more easily degraded under long-term ultraviolet irradiation, thereby affecting its long-lasting UV protection performance.

[0146] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A highly transparent rare earth ultraviolet shielding material, characterized in that: Includes primer and topcoat; The primer comprises the following components in parts by weight: 20-50 parts of porous polyetherimide coated rare earth silicate material, 10-50 parts of a first aqueous resin, 0.1-5 parts of a first pre-dispersant, 1-10 parts of a first auxiliary agent, and 10-30 parts of deionized water; The top coating comprises the following components in parts by weight: 20-50 parts of a highly transparent rare earth shielding material, 10-50 parts of a second aqueous resin, 0.1-5 parts of a second pre-dispersant, 1-10 parts of a second auxiliary agent, and 10-30 parts of deionized water; Among them, rare earth silicates are (La a Y b Sm c Dy d )2Si2O7, 0<a,b,c,d<1, a+b+c+d=1; high transparent rare earth shielding material is La m Ce n Y x Al2B2SiO8(OH)2,0 <m,n,x<0.67,m+n+x=0.67。 2. The highly transparent rare earth ultraviolet shielding material according to claim 1, characterized in that: The porous polyetherimide-coated rare earth silicate material is prepared by the following method: 1) Weigh rare earth oxide and silicon oxide, mix them evenly according to a certain proportion, and then add deionized water to mix; 2) putting the prepared material in step 1) into a ball mill for ball milling, taking out the material after the milling, and drying it to obtain a rare earth silicate precursor; 3) The rare earth silicate precursor obtained in step 2) is placed in a tube furnace and calcined to obtain rare earth silicate (La a Y b Sm c Dy d )2Si2O7; 4) grinding the rare earth silicate obtained in step 3); 5) dissolving the polyetherimide particles in N-methylpyrrolidone to obtain a transparent dark yellow polyetherimide solution; 6) Weigh rare earth silicate and polyetherimide solution, mix them evenly and stir them ultrasonically, centrifuge and dry after the reaction to obtain a porous polyetherimide-coated rare earth silicate material.

3. The highly transparent rare earth ultraviolet shielding material according to claim 2, characterized in that: In step 2), the ball milling speed is 300-600 r / min, the ball milling reaction is 12-18 hours, and the mixture is dried at 60-80° C. for 8-12 hours; In step 3), the calcination temperature is 1200-1500° C. and the calcination time is 3-6 hours; In step 4), the particle size after grinding is 500-800 nm; In step 5), the dissolution temperature of the polyetherimide particles is 50-70°C; In step 6), ultrasonic stirring is performed for 20-60 minutes, and the drying temperature is 60-80°C.

4. The highly transparent rare earth ultraviolet shielding material according to claim 2, characterized in that: In step 1), the molar ratio of rare earth oxide to silicon oxide is 1:2; The rare earth oxide is a mixture of lanthanum oxide, yttrium oxide, dysprosium oxide and samarium oxide; In step 6), 50-70 parts of rare earth silicate and 30-50 parts of polyether imide solution are included by weight.

5. The highly transparent rare earth ultraviolet shielding material according to claim 1, characterized in that: The highly transparent rare earth shielding material is prepared by the following method: 1) Weigh boric acid, silicon oxide, rare earth oxide and aluminum oxide into a ball mill, and add deionized water to mix; 2) putting the prepared materials in step 1) into a ball mill for ball milling; 3) The ball-milled material in step 2) is filtered, washed and dried to obtain La m Ce n Y x Al2B2SiO8(OH)2 powder is then placed in a tube furnace and calcined to obtain a block of La m Ce n Y x Al2B2SiO8(OH)2; 4) Add deionized water to the material obtained in step 3), and then add block La m Ce n Y x A grinding dispersant with a mass percentage of 1-8% of Al2B2SiO8(OH)2 is ground to a particle size of ≤100nm to obtain a highly transparent rare earth shielding material slurry; 5) The highly transparent rare earth shielding material slurry obtained in step 4) is formed into nano-scale powder by a spray dryer.

6. The highly transparent rare earth ultraviolet shielding material according to claim 5, characterized in that: In step 1), the molar ratio of boric acid: silicon oxide: aluminum oxide: rare earth oxide is 1:1:1:0.67; the rare earth oxide is a mixture of lanthanum oxide, cerium oxide and yttrium oxide; In step 2), the ball milling speed is 300-800 r / min, and the ball milling is 8-16 hours; In step 3), the drying temperature is 60-80°C, the calcination temperature is 400-600°C, and the calcination time is 3-6 hours; In step 4), the grinding dispersant is fatty acid polyethylene glycol ester; Step 5) The powder particle size obtained after spray drying is 400-600nm.

7. The highly transparent rare earth ultraviolet shielding material according to claim 1, characterized in that: The first water-based resin and the second water-based resin are both selected from one or more of acrylic resin, polyurethane resin, pure acrylic emulsion, and silicon-modified acrylic emulsion; The first pre-dispersant and the second pre-dispersant are both selected from one or more of BYK-2013, BYK-190, sodium hexametaphosphate, sodium pyrophosphate, and polyvinyl alcohol; The first auxiliary agent and the second auxiliary agent are both selected from one or more of a wetting agent, a thickener, a leveling agent, a defoaming agent, an anti-settling agent, and a film-forming auxiliary agent.

8. A method for preparing a highly transparent rare earth ultraviolet shielding material according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: 1) Preparation of primer 1.1) Weigh the first aqueous resin, the first pre-dispersant and deionized water and stir and disperse them for 60-90 minutes; 1.2) adding the porous polyetherimide-coated rare earth silicate material to step 1.1) and stirring and dispersing for 60-90 minutes, then adding the first auxiliary agent and continuing stirring for 10-30 minutes to prepare a primer; 2) Preparation of topcoat 2.1) Weigh the second aqueous resin, the second pre-dispersant and deionized water and stir and disperse for 60-90 minutes; 2.2) Add the highly transparent rare earth shielding material to step 2.1) and stir and disperse for 60-90 minutes, then add the second auxiliary agent and continue stirring for 10-30 minutes to obtain the top coating.

9. An application of the highly transparent rare earth ultraviolet shielding material according to any one of claims 1 to 7 in the fields of home textiles, outdoor products, clothing fabrics and industrial textiles, characterized in that: During application, the primer is scraped on the fabric surface, and cured at 130-150°C for 3-5 minutes to complete the coating of the primer; the topcoat is scraped on the surface of the primer, and cured at 130-150°C for 3-5 minutes to complete the coating of the topcoat.

10. The use of the highly transparent rare earth ultraviolet shielding material according to claim 9 in the fields of home textiles, outdoor products, clothing fabrics and industrial textiles, characterized in that: The weight of the primer coating is 40-55g / m 2 The weight of the intermediate and top coatings should be kept at 15-25g / m 2 between.